Cytofluorimetric Platelet Analysis - Carubbi, Cecilia; Masselli, Elena; Gesi, Marco; Galli, Daniela; Mirandola, Prisco; Vitale, Marco; Gobbi, Giuliana (Seminars in Thrombosis and Hemostasis, 2014)
Blood platelets are highly specialized cells that drive hemostatic events and tissue repair mechanisms at the site of vascular injury. Their peculiar morphology and certain functional characteristics can be analyzed by flow cytometry (FCM). Specifically, platelet activation, a hallmark of prothrombotic states and inflammatory conditions, is associated with changes in expression of both surface and intracellular antigens that are recognized by specific monoclonal antibodies. Assessment of platelet activation status as ex vivo or in vitro reactivity to specific agonists has become relevant in particular conditions (namely, cardiovascular diseases, hematological malignancies, monitoring of pharmacological antiaggregation). In addition, aberrant surface marker expression that characterizes inherited and acquired platelet function disorders is also detected by FCM. This review discusses the main applications of FCM in platelet analyses, which are relevant for both research and clinical settings.
Keywords: platelet disorders; flow cytometry; megakaryocytes; platelets; thrombosis